A New Mixed Method for the Stokes Equations Based on Stress-Velocity-Vorticity Formulation (Journal of Mathematical Study, 2019)
In this paper, we develop and analyze a mixed finite element method forthe Stokes flow. This method is based on a stress-velocity-vorticity formulation. Anew discretization is proposed: the stress is approximated using the Raviart-Thomaselements, the velocity and the vorticity by piecewise discontinuous polynomials. Itis shown that if the orders of these spaces are properly chosen then the advocatedmethod is stable. We derive error estimates for the Stokes problem, showing optimalaccuracy for both the velocity and vorticity.